Modulation of proteasomal activity required for the generation of a cytotoxic T lymphocyte-defined peptide derived from the tumor antigen MAGE-3. - Valmori, D; Gileadi, U; Servis, C; Dunbar, P; Cerottini, J; Romero, P; Cerundolo, V; Lévy, F (1999)
We have analyzed the presentation of human histocompatability leukocyte antigen-A*0201-associated tumor peptide antigen MAGE-3271-279 by melanoma cells. We show that specific cytotoxic T lymphocyte (CTL)-recognizing cells transfected with a minigene encoding the preprocessed fragment MAGE-3271-279 failed to recognize cells expressing the full length MAGE-3 protein. Digestion of synthetic peptides extended at the NH2 or COOH terminus of MAGE-3271-279 with purified human proteasome revealed that the generation of the COOH terminus of the antigenic peptide was impaired. Surprisingly, addition of lactacystin to purified proteasome, though partially inhibitory, resulted in the generation of the antigenic peptide. Furthermore, treatment of melanoma cells expressing the MAGE-3 protein with lactacystin resulted in efficient lysis by MAGE-3271-279-specific CTL. We therefore postulate that the generation of antigenic peptides by the proteasome in cells can be modulated by the selective inhibition of certain of its enzymaticactivities.